KICHIK GURUHLARDA ISHLASH METODIKASI - Pirnazar Davronov (INTEGRATION OF SCIENCE, EDUCATION AND PRACTICE. SCIENTIFIC-METHODICAL JOURNAL, 2021)
In this report described an idea of interconnection using methods in teaching traditional and advanced pedagogical technology. This connection indicated in teaching mathematics by examples.